ХАРАКТЕРИСТИКА ІЗОЛЯТУ ВІРУСУ ЖОВТОЇ МОЗАЇКИ КВАСОЛІ, ВИДІЛЕНОГО З ЛЮПИНУ ЖОВТОГО - Пиріг, О. В.; Дмитрук, О. О.; Бова, Т. О. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2016)
The comparative characteristic of biological, physical and chemical, and antigenic properties of the isolate bean yellow mosaic virus (BYMV) isolated from yellow lupine on the Chernihiv region territory. It is found that properties of BYMV-P isolate differ from the typical properties of strain BYMV (B-25) and isolates studied in Ukraine.